Evaluation of Inflammatory Markers in a Large Sample of Obstructive Sleep Apnea Patients without Comorbidities - Izolde Bouloukaki; Charalampos Mermigkis; Nikolaos Tzanakis; Eleftherios Kallergis; Violeta Moniaki; Eleni Mauroudi; Sophia E. Schiza (Hindawi Limited, 2017)
Systemic inflammation is important in obstructive sleep apnea (OSA) pathophysiology and its comorbidity. We aimed to assess the levels of inflammatory biomarkers in a large sample of OSA patients and to investigate any correlation between these biomarkers with clinical and polysomnographic (PSG) parameters. This was a cross-sectional study in which 2983 patients who had undergone a polysomnography for OSA diagnosis were recruited. Patients with known comorbidities were excluded. Included patients (n=1053) were grouped according to apnea-hypopnea index (AHI) as mild, moderate, and severe. Patients with AHI < 5 served as controls. Demographics, PSG data, and levels of high-sensitivity C-reactive protein (hs-CRP), fibrinogen, erythrocyte sedimentation rate (ESR), and uric acid (UA) were measured and compared between groups. A significant difference was found between groups in hs-CRP, fibrinogen, and UA. All biomarkers were independently associated with OSA severity and gender (p<0.05). Females had increased levels of hs-CRP, fibrinogen, and ESR (p<0.001) compared to men. In contrast, UA levels were higher in men (p<0.001). Our results suggest that inflammatory markers significantly increase in patients with OSA without known comorbidities and correlate with OSA severity. These findings may have important implications regarding OSA diagnosis, monitoring, treatment, and prognosis. This trial is registered with ClinicalTrials.gov number NCT03070769.